Internationalisation of pharmaceutical retail sector: growth opportunities in emerging markets. (4th June 2010) - Karhu, Anna; Yla-Kojola, Anna-Mari
World pharmaceutical markets are growing and retailers are looking for new markets abroad. This internationalisation pattern offers an interesting topic for research. The growth of the market is shifting from developed markets to emerging ones. Russia is one of the countries where the growth of the pharmaceutical markets is expected to be strong in the future. This study focuses on describing the current competitive situation in the Russian pharmaceutical retail sector, enlightening the possibilities this market has to offer for foreign pharmaceutical retail companies. The results of the study show that it is evident that the market potential is promising in the Russian pharmaceutical retail sector, as the sector has just started to develop nationwide. However, the Russian market has its own peculiarities, which the European pharmaceutical retailers should take into account when entering the market.